Indonesia’s Makan Bergizi Gratis Program: Nutrition, Food Safety, and Hygiene Management - Eunjeong Park; Ki Han Kwon (Media Gizi Indonesia, 2026)
Introduction: Indonesia introduced the Free Nutritious Meals (Makan Bergizi Gratis, MBG) program in January 2025 to address stunting, undernutrition, and the double burden of malnutrition among children and vulnerable groups. Aims: This review evaluates early nutritional outcomes, food safety, hygiene management, and operational challenges of MBG. Methods: A narrative review of peer-reviewed studies, policy documents, government reports, and international agency materials published up to September 2025 was conducted. Sources were synthesized by three domains: nutritional improvement, food safety and hygiene management, and operational and governance challenges. Results: Early evidence suggests improvements in dietary diversity and protein and iron intake, with potential benefits for growth, attendance, and learning concentration. However, reported foodborne illness incidents indicate weaknesses in kitchen capacity, cold-chain logistics, food handling, and local monitoring. Low budget absorption and regional disparities further challenge rapid nationwide scale-up. Conclusions: Strengthening standardized menus, kitchen certification, food-safety protocols, real-time monitoring, and inter-ministerial coordination is essential to improve MBG implementation and sustainability